REVOLUSI INDUSTRI 4.0 DALAM PERSPEKTIF HUKUM PERSAINGAN USAHA DI INDONESIA - Osgar S Matompo; Moh Nafri (Fakultas Hukum Universitas Muhammadiyah Palu, 2020)
The Industrial Revolution 4.0 revolutionized the movement of the world economy. If you do not prepare yourself from now on, you will be left far behind in the world economy. Government intervention in monopoly and oligopoly markets aims to influence prices, the amount produced, and the distribution of income from economic activities. Intervention is carried out in 2 ways, namely: regulation and anti-monopoly law. In this research, the recommendation is that the Government must be able to create regulations that encourage the development of the digitalization economy as a strategy. Such as the policy of convenience in financing startup businesses, tax incentives and guidance for SMEs. The government also needs to increase the development of telecommunications infrastructure in small areas so as to minimize the imbalances that occur. Keywords: Business competition. Industrial Revolution